Focusing on the subsidized health regime in colombia (2003)
Based on the results of the project "Evaluation of the Processes of the Subsidized health regime" in Colombia, a reflection is presented about the beneficiary selection system-Sisben as a tool to affiliate people to the subsidized health regime. The multiple interpretations which have been given to the Sisben as an instrument to focalize the health services in the poorest populations, are documented and analyzed. This has been interpreted, amongst others, as a measure of the magnitude of poverty, as an approximate indicator of resources or income, or as an evaluation of fulfillment of needs. It was found that amongst the 19 million of poor people living in Colombia in 1997, less than half of them, 8,9 million, have been included in levels 1 and 2 of Sisben, which represents an exclusion error of 53,1%. Of the 10,6 million persons classified in these levels, 1,6 % are not poor, giving an inclusion error of 14.9%. The exclusion errors are much more serious then the inclusion ones, because they mean a denial of equal rights and services for all those who are in similar conditions, according to the criteria for assignation of subsidies.